Предмет: Математика,
автор: and77d
13+7х+12-9х=9
3х+5=2х+7
-6(2Х+1)= -42-3х
1,6(х-3)-0,6(2х-8) =0
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
13+7х+12-9х=9
-2x + 25 = 9
2x = 25 - 9
2x = 16
x = 16 : 2
x = 8
3х+5=2х+7
3x - 2x = 7 - 5
x = 2
-6(2Х+1)= -42-3х
-12x - 6 = -42 - 3x
12x - 3x = 42 - 6
9x = 36
x = 36 : 9
x = 4
1,6(х-3)-0,6(2х-8) =0
1,6x - 4,8 - 1,2x + 4,8 = 0
0,4x = 0
x = 0
Автор ответа:
1
Відповідь:
Покрокове пояснення:
13+7х+12-9х=9
7х-9х=9-13-12
-2х= -16
х=8
зараз інші напишу
Похожие вопросы
Предмет: Английский язык,
автор: МАКС18
Предмет: Русский язык,
автор: 89232774729gfif
Предмет: Русский язык,
автор: olga652215
Предмет: Математика,
автор: Даниилка2006
Предмет: Алгебра,
автор: Наташечка111